Bag‐1 mediates glucocorticoid receptor trafficking to mitochondria after corticosterone stimulation: Potential role in regulating affective resilience. Issue 2 (21st October 2020) - Luo, Shaolei; Hou, Yangyang; Zhang, Yaping; Feng, Lei; Hunter, Richard G.; Yuan, Peixiong; Jia, Yue; Li, Haoran; Wang, Gang; K. Manji, Husseini; S. McEwen, Bruce; Xiao, Chunjie; et al.
Abstract: Molecular abnormalities within the Glucocorticoid Receptor (GR) stress signaling pathway involved in dysfunction of mitochondria and confer vulnerability to stress‐related psychiatric disorders. Bcl‐2 associated athanogene (Bag‐1) is a target for the actions of mood stabilizers. Bag‐1 interacts with GR, thereby regulating glucocorticoid function. In this study, we investigate the potential role of Bag‐1 in regulating GR translocation into mitochondria. Corticosterone (CORT) treatment significantly enhanced Bag‐1/GR complex formation and GR mitochondrial translocation in cultured rat cortical neurons after treatment for 30 min and 24 hr. By contrast, after stimulation with CORT for 3 days, localization of the Bag‐1/GR complex and mitochondrial GR were reduced. Similar results were obtained in mice, in which administrated CORT in drinking water for 21 days significantly impaired the GR levels in the mitochondria, while Bag‐1 over‐expression rescued this reduction. Furthermore, chronic CORT exposure led to anhedonia‐like and depression‐like behaviors in the sucrose‐consumption test and forced swimming test, and these behaviors were rescued by Bag‐1 over‐expression. These results suggest that Bag‐1 mediates GR trafficking to mitochondria and regulates affective resilience in response to a CORT increase and provide potential insight into the mechanisms by which Bag‐1 and GR could contribute to the physiology and pathogenesis of psychiatric disorders in response to the change of stress hormone. Abstract : Bag‐1 is a target of mood stabilizers, which can regulating the function of GR. The abnormalities of GR stress signaling pathway involved in dysfunction of mitochondria and stress‐mediated psychiatric disorders. However, the process of GR translocation into mitochondria is unknown. We found that acute corticosterone treatment enhanced Bag‐1/GR complex formation and GR mitochondrial translocation. By contrast, chronic corticosterone reduced Bag‐1/GR complex and mitochondrial GR levels, while Bag‐1 over‐expression rescued these reductions and the depression‐like behaviors induced by chronic corticosterone. Our findings suggested that Bag‐1 is critical for GR trafficking to mitochondria and regulates affective resilience in response to corticosterone stimulation.